2019
DOI: 10.1002/wsb.985
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification error associated with classifications of white‐tailed deer images

Abstract: Camera traps are widely used to monitor wildlife, with important management decisions often relying on interpretation of these data. Animal misidentifications are known to be an important source of error in wildlife surveys that require the identification of unique individuals from camera-trap data; however, the practice of broadly classifying animal images according to sex or age has received less critical attention despite the significant potential for misidentification error under certain circumstances. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Most identification mistakes occurred between species with least phenotypic distinctiveness, for instance when observers confused Plains and Hartmann's mountain zebras. This finding is consistent with other camera trap studies showing that accurate mammal classifications are difficult to obtain where a range of similar-looking species occur sympatrically (Gooliaff and Hodges 2018), or individuals of a particular species exhibit little distinctiveness (Güthlin et al 2014;Newbolt and Ditchkoff 2019). Following our study, observers commented that animal orientation in the image frame (broad side vs. frontal vs. rear views) as well as 'crowdedness', i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most identification mistakes occurred between species with least phenotypic distinctiveness, for instance when observers confused Plains and Hartmann's mountain zebras. This finding is consistent with other camera trap studies showing that accurate mammal classifications are difficult to obtain where a range of similar-looking species occur sympatrically (Gooliaff and Hodges 2018), or individuals of a particular species exhibit little distinctiveness (Güthlin et al 2014;Newbolt and Ditchkoff 2019). Following our study, observers commented that animal orientation in the image frame (broad side vs. frontal vs. rear views) as well as 'crowdedness', i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research suggests not, showing that inter-observer variance can greatly affect the reliability of results obtained when multiple human observers are expected to perform the same task. Studies found considerable inconsistencies in the information obtained, be it during the identification of mammalian species or unique individuals from camera trap footage (Gooliaff and Hodges 2018;Johansson et al 2020), or the classification of population characteristics (Newbolt and Ditchkoff 2019). It is also clear that different factors such as camera type (Randler and Kalb 2018) and observer experience can influence the results (Burns et al 2018;Katrak-Adefowora Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A deer was un-categorized if only a portion of the deer was visible, such as a tail or leg. Three of us (AMS, TKF, and VHM) identified all photos; we trained together and repeatedly interacted on questionable categorizations to minimize misclassifications (Newbolt and Ditchkoff 2019).…”
Section: Methodsmentioning
confidence: 99%
“…We visually leveled each camera, and tested FOV using a standard visibility marker flag (Hofmeester et al 2017, Wearn and Glover-Kapfer 2017, Moll et al 2020; none of the camera models detected our visibility marker flag at >3 m. To evaluate potential effects of aligned cameras on station performance, we placed like model cameras directly across from one another, and perpendicular to maintained paths and trails (Figure 1). To examine the performance of stations with staggered cameras, we faced the cameras directly across a maintained path or trail and offset them by 4.6 m. Stations were not baited (i.e., to minimize bias [Newbolt et al 2017, Fidino et al 2020) and set up to capture F I G U R E 1 Diagram of a 2 paired camera station; alignment options included alternating camera models between aligned camera stations (4.6 m across from each other and perpendicular to the trail) and staggered camera stations (4.6 m across from each other and perpendicular to the trail and offset by 4.6 m) evaluated at Kibbe Station, Warsaw, Illinois, USA, summer 2018. Paired camera stations were separated by ≥9 m to ensure independence (i.e., flash from one station would not impact images at subsequent stations) between successive stations, and we alternated camera station models across treatments to minimize environmental bias.…”
Section: Evaluation Of Camera Model and Alignmentmentioning
confidence: 99%